GULMA ECENG GONDOK (EICHORRNIA CRASSIPES) SEBAGAI PUPUK ORGANIK FERMENTASI TRICHODERMA SPP. PADA TANAMAN PADI DI KELURAHAN PRAPEN KECAMATAN PRAYA KABUPATEN LOMBOK TENGAH: Water Hyacinth Weed (Eichorrnia Crassipes) As Fermented Organic Fertilizer Trichoderma spp. On Rice Plants In Prapen Village, Praya District, Central Lombok Distri - Apzani, Wawan; Haryantini, Baiq Azizah; Sunantra, I Made; Wardhana, Agung Widya; Arifin, Zainal; Baharuddin, Baharuddin; Zainab, Siti (Al-Amal: Jurnal Pengabdian Masyarakat, 2023)
Water hyacinth (Eichorrnia crassipes) is a weed whose presence is very disturbing in the Batujai Dam area. The government has made various efforts to reduce its growth, but the population is increasing day by day. This activity aims to utilize water hyacinth which grows very high in the Batujai Dam area as an alternative fertilizer to reduce the use of synthetic chemical fertilizers on plants. The method used is a presentation method and then followed by practice for making organic fertilizer. Participants were given material about the impact of the abundance of water hyacinth weeds and their effects and benefits, then they were given training directly using fermented by Trichoderma spp. for 14 days. The result of this activity is that farmers can utilize nuisance weeds into fertilizer which can increase soil and plant fertility and can reduce the weed population in waters so that the sedimentation rate is reduced. It is hoped that farmers and the community will continue to use this weed so that the Batujai Dam area can be free from water hyacinth weeds and soil fertility can increase and farmers can reduce the use of synthetic chemical fertilizers